Inclusive Android-Based Solution: E-Book Reader Application with Text-To-Speech for Empowering People with Disabilities - Muhammad Fathan Ramadhan; Suhirman (INOVTEK Polbeng - Seri Informatika, 2024)
One of the growing innovations is an e-book reader application equipped with a text-to-speech (TTS) feature. This research aims to design and develop an e-book reader application that can convert text into speech. The application is designed using the Agile software development method, which allows for iterations and continuous improvements based on user feedback. The main features of this application include the ability to adjust the speed and type of voice, as well as support for various e-book formats such as ePub, PDF, and TXT. The TTS implementation leverages available APIs, enabling high-quality and natural text-to-speech conversion. The evaluation of this application shows that users feel supported by the TTS feature, and the method used is quantitative. Testing results and feedback from early users indicate that this application not only improves accessibility but also provides a more flexible and comfortable reading experience. Therefore, this text-to-speech e-book reader application is expected to become an effective solution in supporting literacy and accessibility for all groups.